Globalization, development, and mobility of technical talent: India and Japan in comparative perspectives - Anthony P. D'Costa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
The objective here is to understand how the mobility of technical talent might be changing the structural relationship between rich and poor countries. This paper examines the under-researched relationship between India and Japan in the context of globalization, migration, and developmental impact with demographic, immigration, and innovation policy issues as key themes. By focusing on the export of technical talent, I argue that India could tap its overseas `brain bank' by diversifying IT export markets, create epistemic networks, meet impending skill shortages in Japan, and induce long-term innovative capability. Immigration reforms and freer movement of talent will be critical.
Keywords: F22; J24; O19; O57; 330; international migration; technical talent; IT industry; innovation and development; `brain bank'; India; Japan; Brain Drain; Informationstechnik; Globalisierung; Indien; Japan